Science, values and politics: an insider’s reflections on corporate crime research - Yeager, Peter Cleary (Crime, law and social change, 2009)
Diverse social and political forces have long shaped research on corporate crime and its social control in the U.S., and they have responded to this work in plural and contradictory ways. These forces range from the abstract and institutional to the local and personal. In this essay, I reflect on my three decades of research experience in this arena in an examination of these forces and their implications for research and public policy. More overtly than other forms of criminological research, the study of corporate lawbreaking has conjoined issues of values and politics with issues of science. This feature of the work has made consistently problematic such foundational questions as how to define the subject of inquiry, how to study it, and how to communicate about it. While this volatility has contributed to the ongoing marginalization of this research stream in both academic criminology and regulatory policy, it has also created a certain intellectual dynamism that should attract future generations of investigators to these questions, and to greater cross-disciplinary efforts to address them. Such developments may even pave the way to greater consideration of such research by policy-makers, should socioeconomic conditions in the U.S. and around the world raise the public salience of corporate wrongdoing.***‘Why do you want to study corporate managers? We know how they think.’***‘…a book entitled Corporate Crime automatically puts us on guard to defend the corporations…such a book should never have been written in the first place.’